Characteristics and clinical outcomes of patients with pre-delta, delta and omicron SARS-CoV-2 infection in Indonesia (2020-2023): a multicentre prospective cohort studyResearch in context - Anis Karuniawati; Ayodhia Pitaloka Pasaribu; Gilbert Lazarus; Vera Irawany; Dwi Utomo Nusantara; Robert Sinto; Suwarti; Maulana Jamil Nasution; Ferawati; Muhammad Riza Lubis; Eka Nurfitri; Mutiara Mutiara; et al. (Elsevier, 2024)
Summary: Background: Limited data exist from southeast Asia on the impact of SARS-CoV-2 variants and inactivated vaccines on disease severity and death among patients hospitalised with COVID-19. Methods: A multicentre hospital-based prospective cohort was enrolled from September 2020 through January 2023, spanning pre-delta, delta, and omicron periods. The participant hospitals were conveniently sampled based on existing collaborations, site willingness and available study resources, and included six urban and two rural general hospitals from East Nusa Tenggara, Jakarta, and North Sumatra provinces. Factors associated with severe disease and day-28 mortality were examined using logistic and Cox regression. Findings: Among 822 participants, the age-adjusted percentage of severe disease was 26.8% (95% CI 22.7-30.9) for pre-delta, 50.1% (44.0-56.2) for delta, and 15.2% (9.7-20.7) for omicron. The odds of severe disease were 64% (18-84%) lower for omicron than delta (p < 0.001). One or more vaccine doses reduced the odds of severe disease by 89% (65-97%) for delta and 98% (91-100%) for omicron. Age-adjusted mortality was 11.9% (8.8-15.0) for pre-delta, 24.4% (18.8-29.9) for delta and 9.6% (5.2-14.0) for omicron. The day-28 cumulative incidence of death was lower for omicron (9.2% [5.6-13.9%]) than delta (28.6% [22.0-35.5%]) (p < 0.001). Severe disease on admission was the predominant prognostic factor for death (aHR34.0 [16.6-69.9] vs mild-or-moderate; p < 0.001). After controlling for disease severity on admission as an intermediate, the risk of death was 48% (32-60%) lower for omicron than delta (p < 0.001); and 51% (38-61%; p < 0.001) lower for vaccinated participants than unvaccinated participants overall, and 56% (37-69%; p < 0.001) for omicron, 46% (−5 to 73%; p = 0.070) for pre-delta (not estimable for delta). Interpretation: Infections by omicron variant resulted in less severe and fatal outcomes than delta in hospitalised patients in Indonesia. However, older, and unvaccinated individuals remained at greater risk of adverse outcomes. Funding: University of Oxford and Wellcome Trust.